Letter from J. Ross Snowden to James Curtis Booth, March 23, 1854 - Snowden, James Ross (1854)
James Ross Snowden (1809-1878), who was treasurer of the U.S. Mint at the time, requests James Curtis Booth (1810-1888) to locate 100 perfect specimens of a proposed new cent piece and to write a report.
Keywords: Booth, James Curtis, 1810-1888; Snowden, James Ross, 1809-1878; United States Mint; Mint of the United States; Coins